El papel de la información en la lucha contra la delincuencia organizada transnacional - Sansó-rubert, Daniel (UNISCI Discussion Papers, 2006)
Having proved that the measures used up to now in the fight against the new dimension of transnational organized crime are not efficient in many respects, it is necessary to use new mechanisms or to improve the existing ones, in order to adequate state capabilities to the new strategic and operational scenario. In this context in which transnational organized crime represents a first order threat, the means for collecting information and elaborating intelligence are indispensable elements. The choice of covert operations and agents as a topic for reflection is due to the beliefs that they can become effective instruments, once they are properly articulated and defined.